Evaluation of the photoprotective activity of the ethanolic extract of Rhaphiodon echinus Schauer (Research, Society and Development, 2020)
The aim of the present study was to evaluate, in vitro, the photoprotective activity of the ethanolic extract of Rhaphiodon (R.) echinus. The experiment was carried out with different concentrations of the natural product (50, 100, 500 and 1000 μg / mL). Through scans with the aid of an spectrophotometer, in the ranges (290 to 320 nm) with 5 nm intervals. The data were submitted to Mansur et al. (1986) equation. According to the results obtained, only the two highest concentrations (500 μg / mL and 1000 μg / mL) showed considerable photoprotection values and above the minimum protection factor of 6 (SPF), being 23.65 and 25.00 respectively. Thus, the photoprotective activity of the ethanol extract, in vitro, of R. echinusdemonstra uma importante característica bioativa. Além disso, o resultado ainda sugere um possível uso dessa planta em formulações fitocosméticas, uma vez que o uso de plantas como fotoprotetores é uma das alternativas acessíveis.